Material removal model of chemical mechanical polishing for fused silica using soft nanoparticles. Issue 9 (February 2017) - Liu, Defu; Chen, Guanglin; Hu, Qing
Abstract Fiber arrays are used to connect arrayed waveguide chips. The end-faces of fiber array components are multi-materials non-uniform surfaces. Their low polishing quality has become a bottleneck that restricts coupling performance of integrated photo-electronic devices. The chemical mechanical polishing (CMP) is normally used to improve the polishing quality of the end-faces of fiber array components. It is very important to optimize process parameters by researching the mechanical behavior of nanoparticles and material microstructure evolution on the CMP interfaces. Based on the elastic and hyper-elastic contact of the soft polishing nanoparticles with fused silica and polishing pad, respectively, the material removal mechanism at molecular scale of polishing process for fused silica using nanoparticles is investigated, and the material removal rate model is also derived by using Arrhenius theory and molecule vibration theory. Theoretical and experimental results show that the material is mainly removed by the interfacial tribo-chemical effect between polishing nanoparticles and fused silica during CMP process. The penetration depth of a single nanoparticle inside the fused silica is at molecular scale, and the superficial molecules of fused silica are removed by chemical reactions because of enough energy obtained. The material removal rate of fused silica during CMP process is determined by the polishing pressure, the chemical reagents and its concentration, and the relative movement speed between the fused silica workpiece and the polishing pad.